2021
DOI: 10.1021/acs.nanolett.1c02502
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Site-Promoted Single-Atomic Cu Catalyzes Electrochemical CO2 Methanation

Abstract: Developing an efficient catalyst for the electrocatalytic CO 2 reduction reaction (CO 2 RR) is highly desired because of environmental and energy issues. Herein, we report a single-atomic-site Cu catalyst supported by a Lewis acid for electrocatalytic CO 2 reduction to CH 4 . Theoretical calculations suggested that Lewis acid sites in metal oxides (e.g., Al 2 O 3 , Cr 2 O 3 ) can regulate the electronic structure of Cu atoms by optimizing intermediate absorption to promote CO 2 methanation. Based on these theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 53 publications
2
104
0
Order By: Relevance
“…Intensive consumption of traditional fossil fuels has been causing increased atmospheric carbon dioxide (CO 2 ), one of the main greenhouse gases, accounting for the continously going up of the global temperature [1][2][3]. Electrochemical catalysis provides a cost-effective and energy-efficient method for the mitigation of the environmental and energy concerns by directly converting CO 2 to valuable fuels and chemicals under ambient condition [4][5][6][7].…”
Section: Instructionmentioning
confidence: 99%
“…Intensive consumption of traditional fossil fuels has been causing increased atmospheric carbon dioxide (CO 2 ), one of the main greenhouse gases, accounting for the continously going up of the global temperature [1][2][3]. Electrochemical catalysis provides a cost-effective and energy-efficient method for the mitigation of the environmental and energy concerns by directly converting CO 2 to valuable fuels and chemicals under ambient condition [4][5][6][7].…”
Section: Instructionmentioning
confidence: 99%
“…S2, ESI †). [26][27][28] The wavelet transform (WT) contour plot of SA-Ni-NC had only one intensity maximum at 5.6 ÅÀ1 , which was assigned to the Ni-N bonds rather than Ni-Ni scattering (8.2 ÅÀ1 ). These results clearly prove the dispersion of Ni-N 4 species in SA-Ni-NC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they also demonstrated that the Lewis acid site in p‐Al 2 O 3 alters the electronic structure of Cu, which makes the single atom Cu more smoothly for producing CH 4 as the main product (Figure 5G,H). 95 In addition to LD metal oxide, the LD metal hydroxide is also used to support single atoms for ECR. Han et al 97 reported an a ‐Co(OH) 2 nanosheets supported Ir SAC for ECR, which shows the FE of CO could reach 97.6% with a TOF of 38,290 h −1 in aqueous electrolyte.…”
Section: Ldm Supported Sacsmentioning
confidence: 99%
“…Color code: Cu, brick red; Al, purple; Cr, gray; O, red. Reproduced with permission 95 . Copyright 2021, American Chemical Society.…”
Section: Ldm Supported Sacsmentioning
confidence: 99%